Transcriptomic analysis reveals the inhibitory effect of beta-sitosterol on proliferation of bovine preadipocytes - Lei Jiang; Yuan Wan; Jinhai Pan; Xiaoyu Mao; Xiaolei Sun; Linsen Zan; Hongbao Wang (Animal Biotechnology)
Fat deposition affects beef quantity and quality via preadipocyte proliferation. Beta-sitosterol, a natural small molecular compound, has various functions, such as anti-inflammation, antibacterial, and anticancer properties. The mechanism of action of Beta-sitosterol on bovine preadipocytes remains unclear. This study, based on RNA-seq, reveals the impact of Beta -sitosterol on the proliferation of bovine preadipocytes. Compared to the control group, Beta-sitosterol demonstrated a more pronounced inhibitory effect on cell proliferation after 48 hours of treatment than after 24 hours, as evidenced by the results of EdU staining and flow cytometry. RNA-seq and Western Blot analyses further substantiated these findings. Our results suggest that the impact of Beta-sitosterol on the proliferation of bovine preadipocytes is not significant after a 24-hour treatment. It is only after extending the treatment time to 48 hours that Beta-sitosterol may induce cell cycle arrest at the G2/M phase by suppressing the expression of CCNB1, thereby inhibiting the proliferation of bovine preadipocytes.